A novel role for Teneurin C-terminal Associated Peptide (TCAP) in the regulation of cardiac activity in the Sydney rock oyster, Saccostrea glomerata - Abramov, Tomer; Suwansa-ard, Saowaros; da Silva, Patricia Mirella; Wang, Tianfang; Dove, Michael; O’Connor, Wayne; Parker, Laura; Russell, Fraser D.; Lovejoy, David A.; Cummins, Scott F.; Elizur, Abigail (Frontiers in Endocrinology, 2023)
Teneurin C-terminal associated peptide (TCAP) is an ancient bioactive peptide that is highly conserved in metazoans. TCAP administration reduces cellular and behavioural stress in vertebrate and urochordate models, yet despite numerous studies in higher animals, there is limited knowledge of its role in invertebrates. In particular, there are no studies on TCAP’s effects on the heart of any metazoan, which is a critical organ in the stress response. We used the Sydney rock oyster (SRO) as an invertebrate model to investigate a potential role for sroTCAP in regulating cardiac activity, including during stress. sroTCAP is localized to the neural innervation network of the SRO heart, and demonstrated binding with various heart proteins related to metabolism and stress, including SOD, GAPDH and metabotropic glutamate receptor. Intramuscular injection of sroTCAP (10 pmol) significantly altered the expression of heart genes that are known to regulate remodelling processes under different conditions, and modulated several gene families responsible for stress mitigation. sroTCAP (1 and 10 pmol) was shown to cause transient bradycardia (heart rate was reduced by up to 63% and for up to 40 min post-administration), indicative of an unstressed state. In summary, this study has established a role for a TCAP in the regulation of cardiac activity through modulation of physiological and molecular components associated with energy conservation, stress and adaptation. This represents a novel function for TCAP and may have implications for higher-order metazoans.